Activity budgets, daily energy expenditure and energetic model of Black Brant Branta bernicla nigricans during winter and spring along the Lower Alaska Peninsula - Daniels, Bryan L.; Ward, David H.; Black, Jeffrey M. (Wildfowl, 2019)
Black Brant Branta bernicla nigricans have one of the most specialised of goose diets during the non-breeding season, utilising coastal habitats to up-end and feed on dense beds of intertidal Common Eelgrass Zostera marina. Past studies suggested that Black Brant may not reach energetic requirements during diurnal foraging on eelgrass beds and must use alternate, less energetically beneficial foraging strategies (e.g. searching for and consuming sparse drifting eelgrass and night-time eelgrass bed foraging) to meet energy demands. Time-activity budgets and daily energy expenditure (DEE) were quantified and use of alternate foraging strategies during periods of limited food availability were described for Black Brant along the Lower Alaska Peninsula in Kinzarof and Izembek Lagoons during winter (February–March) and spring (April–May) 2011. Based on 577 instantaneous flock scans across seasons and tide stages, predominant Black Brant activities were vigilance (41%), foraging (33%), comfort (16%) and locomotion (8%). Estimated mean DEE across months and locations was 1,181 ± 110 kJ/day. Flight costs accounted for an estimated 23–46% of expended energy in winter and spring, roosting 22–27%, thermoregulatory costs 13–18%, foraging 8–15% and vigilance 10–17% in spring. Black Brant only met daily energetic requirements by employing alternate foraging strategies, particularly nocturnal foraging, which offset their DEE by 21–43% in winter and 17–28% in spring.